The Transmission Mechanisms of Inflation: An Empirical Study on the ASEAN Economies - Cheng, Ming Yu (1999)
Maintaining low and stable inflation has been the primary goal of most countries, particularly for the fast growing developing countries. Vast great inflation theories, from Classical, Keynesian, Monetary to Structural, carrying different banners and offering different evidence on the causes of inflation. It is of utmost importance to correctly identify the causes of inflation in each economic setting as wrong diagnosis of the nature of the problem will lead to the application of inappropriate cures that might hurt the economy. This study, whenever possible, takes the effort to capture the ideas of major inflation theories in a single dynamic inflation model. An eleven-equation set up with eleven variables in each equation is used for each five ASEAN countries. The ASEAN in this study refers to five original members of ASEAN, namely fudonesia, Malaysia, the Philippines, Singapore and Thailand. The primary mission of this study is to analyze the relative importance of factors that significantly contributed to inflation in each of the ASEAN country. This study also aimed to examine the existence of international as well as intra-ASEAN transmission of inflation to these countries. The objectives of the study were achieved by the estimation of Vector Error Correction Model (VECM) and the analysis of impulse response function as well as variance decomposition for each country. The data for the study consists of quarterly observation from 1973:1 to 1997:11. The results of the study revealed that for the ASEAN economies that showed high and stable economic growth for a sustained period, namely Singapore and Malaysia and which had adopted consistent policy in the country, tended to have relatively low and stable inflation rates. Due to the openness of the countries, external factors such as the rest of the world's inflation rates and the rest of the ASEAN's inflation as well as the exchange rate variable are relatively more important in explaining inflation in these two countries. On the other hand, Indonesia and the Philippines which were burdened by huge foreign debts and had took up inconsistent policy mix to spur the growth in the economy had generally experienced high and variable inflation rates. External and internal factors are important in generating inflation in these two countries. In Thailand, the inflationary analysis was somehow unsteady. The findings could be attributed to the structural shifts arising partly from trade and financial liberalisation in the country, particularly at the end of 1980an.